Oxidative Stability of Lipid Fraction of Cookies Enriched with Chokeberry Polyphenols Extract - Bialek Malgorzata; Rutkowska Jaroslawa; Bialek Agnieszka; Adamska Agata (Polish Journal of Food and Nutrition Sciences)
The effect of incorporation of different contents of chokeberry polyphenols extract (CPE) into cookie recipe on the oxidative stability of the lipid fraction of cookies was determined in the study. Margarine and butter cookies with different contents of CPE were prepared. Contents of primary (Peroxide value, PV) and secondary (Anisidine value, AV; thiobarbituric acid reactive substances, TBARS) lipid oxidation products and fatty acids profile were measured during storage. Different course of lipid degradation depending on both polyphenols content and storage time was shown. Cookies were characterised by a low PV (1.45 and 4.90 meq of O/kg of fat in margarine and butter cookies, respectively). The AV increased during storage both in margarine and in butter cookies. Losses of PUFA in margarine cookies (0.34%) apply mainly to α-linolenic acid. It appears safe to incorporate 100 mg and 250 mg of CPE into margarine cookies stored for 9 weeks and 1000 mg of CPE into butter cookies stored for 9 weeks. The incorporation of 1000 mg CPE into cookies resulted in a significant increase in the intensity of astringent taste, acidic taste, off-taste and off-flavour.